Safety and quality in the Portuguese construction industry - Moura, Helder M. Pinto (2007)
Most construction projects in Portugal do not fully achieve the main management functions, namely safety and quality. Accordingly, the competitiveness of the Portuguese construction industry has been ranked fairly low. A survey was conducted among the main construction stakeholders to help clarify the reasons for this problem. The inquiry used for the survey focused on the characteristics of major projects concluded in the last years and on specific data on the achievement of quality and safety objectives. Research revealed that clients invoked poor task preparation, lack of specific training and the lack of individual protection as the main reasons for construction accidents, while contractors attribute responsibilities to the high risk of the activity. 80th clients and contractors indicate that poor work execution and inadequate design solutions are the main reasons for the lack of quality in construction. Additionally, contractors also attribute external factors and the inadequacy of materiais or products a major contribution for the lack of quality in construction.